The financial services industry and society: the role of incentives/punishments, moral hazard, and conflicts of interests in the 2008 financial crisis - Murray, Noel (2017)
Purpose – This paper aims to present an analysis of the role of financial incentives, moral hazard and conflicts of interests leading up to the 2008 financial crisis. Design/methodology/approach – The study’s analysis has identified common structural flaws throughout the securitization food chain. These structural flaws include inappropriate incentives, the absence of punishment, moral hazard and conflicts of interest. This research sees the full impact of these structural flaws when considering their co-occurrence throughout the financial system. The authors address systemic defects in the securitization food chain and examine the inter-relationships among homeowners, mortgage originators, investment banks and investors. The authors also address the role of exogenous factors, including the SEC, AIG, the credit rating agencies, Congress, business academia and the business media. Findings – The study argues that the lack of criminal prosecutions of key financial executives has been a key factor in creating moral hazard. Eight years after the Great Recession ended in the USA, the financial services industry continues to suffer from a crisis of trust with society. Practical implications – An overwhelming majority of Americans, 89 per cent, believe that the federal government does a poor job of regulating the financial services industry (Puzzanghera, 2014). A study argues that the current corporate lobbying framework undermines societal expectations of political equality and consent (Alzola, 2013). The authors believe the Singapore model may be a useful starting point to restructure regulatory agencies so that they are more responsive to societal concerns and less responsive to special interests. Finally, the widespread perception is that the financial services sector, in particular, is ethically challenged (Ferguson, 2012); perhaps there would be some benefit from the implementation of ethical climate monitoring in firms that have been subject to deferred prosecution agreements for serious ethical violations (Arnaud, 2010). Originality/value – The authors believe the paper makes a truly original contribution. They provide new insights via their analysis of the role of financial incentives, moral hazard and conflicts of interests leading up to the 2008 financial crisis.